Broad climatological variation of surface energy balance partitioning across land and ocean predicted from the maximum power limit - Chirag Dhara; Maik Renner; Axel Kleidon (Geophysical Research Letters)
Abstract Longwave radiation and turbulent heat fluxes are the mechanisms by which the Earth's surface transfers heat into the atmosphere, thus affecting the surface temperature. However, the energy partitioning between the radiative and turbulent components is poorly constrained by energy and mass balances alone. We use a simple energy balance model with the thermodynamic limit of maximum power as an additional constraint to determine this partitioning. Despite discrepancies over tropical oceans, we find that the broad variation of heat fluxes and surface temperatures in the ERA‐Interim reanalyzed observations can be recovered from this approach. The estimates depend considerably on the formulation of longwave radiative transfer, and a spatially uniform offset is related to the assumed cold temperature sink at which the heat engine operates. Our results suggest that the steady state surface energy partitioning may reflect the maximum power constraint.